The effect of tomato pomace powder addition on the biscuit content of bioactive compounds and antioxidant activity during storage - Abohaidra, Abdulwahab Ali; Tlay, Rawaa Houri (Journal of agricultural, environmental and veterinary sciences, 2021)
This research was carried out at the laboratories of the Department of Food Sciences, Faculty of Agriculture, Damascus University, during 2019, where fresh tomato pomace was dried using hot air at a temperature of 40 °C for 24 hours to a moisture content of (14.15%), and then it was ground, and its content of phenols, flavonoids and antioxidant activity were studied. The content of tomato pomace powder of phenols was (248.04 mg gallic/100 g) and of flavonoids (35.94 mg quercetin/100 g) on dry matter basis, and the antioxidant activity was (54.01%). The effect of partial replacement of wheat flour with tomato pomace powder in three ratios (5%, 10% and 15%) on the biscuit contents of phenols, flavonoids and antioxidant activity was studied, along with the effect of storage for 6 months on the content of these compounds. It was observed that the addition of tomato pomace powder resulted in a significant increase (P ≥ 0.05) in the biscuit contents of phenols, flavonoids and the antioxidant activity by increasing the level of addition, The both of biscuits samples (5%) and (10%) showed best sensory acceptance compared to the other samples. Furthermore, the storage process for 6 months exhibited a significant decrease in phenols content and the antioxidant activity, while flavonoids content was not affected.